2020
DOI: 10.1080/03075079.2020.1750583
|View full text |Cite
|
Sign up to set email alerts
|

Placement training and learning outcomes in social work education

Abstract: Field placement has traditionally been an important component of professional and vocational education programmes, and there is a growing interest in workplace experience in higher education programmes in general. In this article, we examine the direct and the indirect links between classroom preparation for placement, placement quality and programme coherence, and the development of student learning outcomes (general competence, knowledge and skills). Using a longitudinal survey of social work students, combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
2
11
0
4
Order By: Relevance
“…Placement opportunities by an HEI are found as the most important factor. The introjected regulation compels the student to seek an HEI that can avoid him/her the guilt of an unsuitable/no job (Caspersen and Smeby, 2020; Silva et al , 2018). This finding agrees with Maringe (2006), who found that the weight given to employment prospects is greatest for students.…”
Section: General Discussion and Theoretical Contributionsmentioning
confidence: 99%
“…Placement opportunities by an HEI are found as the most important factor. The introjected regulation compels the student to seek an HEI that can avoid him/her the guilt of an unsuitable/no job (Caspersen and Smeby, 2020; Silva et al , 2018). This finding agrees with Maringe (2006), who found that the weight given to employment prospects is greatest for students.…”
Section: General Discussion and Theoretical Contributionsmentioning
confidence: 99%
“…Seen as the critical linkage between classroom and practice, field placements are a social work programmatic requirement and are necessary to successfully transition into professional practice (Caspersen & Smeby, 2020;CSWE, 2015). Field placements provide students with exposure to professional work in the "real world" while getting academic support.…”
Section: Social Work Student Stressmentioning
confidence: 99%
“…As the signature pedagogy of social work education (CSWE, 2015), field education is essential to increasing each student's understanding of themselves and how to relate with client systems (Bogo, 2015). With academic support, students can better integrate classroom knowledge with what they are learning in the field placement (Bogo, 2015;Caspersen & Smeby, 2020;Royse et al, 1993). The experiential learning opportunities and academic support provided to students as part of the course are why many students and social work professionals view field placements as the most valuable and essential part of social work academic programming (Smith et al, 2015).…”
Section: Social Work Student Stressmentioning
confidence: 99%
“…Theoretical competences Knowledge of professional terminology, theories, and concepts related to your profession [10,22,[24][25][26]33] Practical competences Correct use of principles and theoretical knowledge in practice Use of information and technology (ICT) Use of mathematics to solve operational problems Knowledge of general economic theoretical concepts and formation of an economic way of thinking Understanding the business reality [9,22,23,33,37,50] Sources: Authors' compilation.…”
Section: Global Competences Skills and Abilities Bibliographical Refe...mentioning
confidence: 99%